Interplay of Language Instruction and Academic Performance of Junior High School Students in Multilingual Classrooms - Rogie A. Saldivar; Jessica M. Alcantara (Future Science / FSH-PH Publications, 2026)
Multilingual classrooms are educational settings where unique challenges and opportunities for language instruction can be found which requires pedagogical practices and approaches that are tailored to the linguistic diversity of students. This study investigated and examined the relationship between the interplay of the language of instruction and the academic performance of junior high school students in linguistically diverse settings like Masbate, with the goal of determining the impact of incorporating students' native languages alongside the target language. This study utilized a mixed-method research design specifically the explanatory-sequential research design. It also used the Kruskal-Wallis test as its statistical tool to analyse the relationship between language instruction methods and the academic performance of students in four content areas. Data on student academic performance and language use by teachers was collected through interview and survey. The participants of this study were 80 secondary teachers from 8 schools in the North and South Districts of Mandaonss. The results revealed a statistically significant relationship between language instruction and students' academic performance with H = 13.753 and a p-value of 0.001032. These findings revealed that the language of instruction, used by teachers, significantly impacts student academic performance in multilingual classrooms. Thus, these support the idea that the use of multilingual approaches that incorporate students' native languages could be a key factor in the achievement of learning for students. Thus, this study suggests that further research should be conducted along with specific effective multilingual strategies to explore their long-term impact on student learning.